The AUX1-AFB1-CNGC14 module establishes a longitudinal root surface pH profile - Serre, Nelson B C; Wernerová, Daša; Vittal, Pruthvi; Dubey, Shiv Mani; Medvecká, Eva; Jelínková, Adriana; Petrášek, Jan; Grossmann, Guido; Fendrych, Matyáš (eLife, 2023)
Plant roots navigate in the soil environment following the gravity vector. Cell divisions in the meristem and rapid cell growth in the elongation zone propel the root tips through the soil. Actively elongating cells acidify their apoplast to enable cell wall extension by the activity of plasma membrane AHA H+-ATPases. The phytohormone auxin, central regulator of gravitropic response and root development, inhibits root cell growth, likely by rising the pH of the apoplast. However, the role of auxin in the regulation of the apoplastic pH gradient along the root tip is unclear. Here, we show, by using an improved method for visualization and quantification of root surface pH, that the Arabidopsis thaliana root surface pH shows distinct acidic and alkaline zones, which are not primarily determined by the activity of AHA H+-ATPases. Instead, the distinct domain of alkaline pH in the root transition zone is controlled by a rapid auxin response module, consisting of the AUX1 auxin influx carrier, the AFB1 auxin co-receptor, and the CNCG14 calcium channel. We demonstrate that the rapid auxin response pathway is required for an efficient navigation of the root tip.
Keywords: Cyclic Nucleotide-Gated Cation Channels; proteiny huseníčku; adenosintrifosfatasy; Arabidopsis; plant biology; Plant Roots; kationtové kanály řízené cyklickými nukleotidy; Arabidopsis Proteins; kyseliny indoloctové; Hydrogen-Ion Concentration; Soil; regulace genové exprese u rostlin; kořeny rostlin; auxin; koncentrace vodíkových iontů; root; A. thaliana; Indoleacetic Acids; Gene Expression Regulation, Plant; Adenosine Triphosphatases; pH; půda